Recovery - adaptation: Strength/power sports - Stone, M. (coachesinfo.com)
The primary goal of the training process is obviously enhanced performance, for the coach/athlete this goal is obviously paramount. However, reaching this goal is not simple; it may be argued that enhancing performance is actually a process of intentionally repeating stimuli (exercise) which result in recovery-adaptation, while avoiding overstress-overtraining. There are basically two methods whereby a coach/athlete can enhance the stimulus- recovery adaptation process: